Various Treatments for Vitiligo: Problems Associated and Solutions - Dhvani M. Lakhani,Ashwini S. Deshpande (Journal of Applied Pharmaceutical Science, 2014)
The present review includes the study of vitiligo, its different types and treatments available into the market. Vitiligo is a skin disorder in which white patches occurs on the skin may be in the form of lesions or on the whole body. These white patches occur due to destruction of colour producing cells melanocytes. Different drugs like methoxsalen, trioxsalen and psoralen are available for the treatment of vitiligo in oral capsule form or topical cream or lotion form. Psoralen with light therapy is also given which is also known as PUVA therapy. Treatment of vitiligo always poses a problem as the patient compliance is less. Most of the times the treatment gets discontinued by the patients as the effect are very slow. This inefficiency leads to frustration in patients. This may be one of the reasons for discontinuation or ‘give up’ by the patients. Some patients also face the problem of additional symptoms or side effect like itching, burning, gastric disturbances etc. This review discusses on all above mentioned issues with problems associated with treatment and the related possible solutions.
Keywords: Vitiligo, Psoralen, PUVA, Melanocyte, treatment.